Catalogo de variedades de papa nativa de Chugay, La Libertad - Peru Catalog of ancestral potato varieties from Chugay, La Libertad - Peru - International Potato Center; Asociación Pataz, Peru; Instituto Nacional de Innovación Agraria (International Potato Center, 2015)
The new Catalog of Ancestral Potato Varieties from Chugay highlights the varietal diversity that farmers conserve on-farm. The bilingual catalog is a first of its kind with detailed information for 129 landraces, including nutritional value and resistance traits. Since the International Year of the Potato (2008) multiple high-quality catalogues have been published for localities in central and southern Peru. Yet, this new catalog is the first for a single district in North Peru. It sets a new benchmark for future inventories and clearly recognizes the role of farmers. The catalog bears witness to a vast ancestral culture and, at the same time, makes a valuable contribution to scientific knowledge. The publication can be used as a baseline inventory to monitor the conservation status of landraces, as a guide for studying new attributes or a source of potential landraces to be promoted for the income generation.